The Amusing Bores - Čale Feldman, Lada (Molière u hrvatskoj kulturi, 2024)
The article deals with one of Molière’s critically rather neglected comedies, the three-act comedy-ballet in verse entitled Les Fâcheux (The Nuisances), which has so far not been translated into the Croatian standard. Due however to a larger project of translations-adaptations of Molière’s comedies in the 18th century Dubrovnik, the comedy was translated and localized in Dubrovnik, under the title Dosadni (The Bores), with some interesting alterations of the original. The Bores is truly amusing, that is comical, and one could say that many of its features announce some of the author’s so-called great comedies, one of them being The Misanthrope, with which it shares the crucial dramaturgical idea: the mundane society that drives the hero mad with its narcissistic obsessions, preventing him from reaching his object of desire. The main difference of The Bores however concerns a different disposition of its target of laughter: here it is not the proponent of sincerity, but rather his opposite, the very incarnation of the ideal of courteous interaction, l’honnête homme in person, completely unaware that he is not the victim of his social circle, but of the internalized norm that he is adamant on preserving at any cost. This interpretation offers a psychoanalytic reading of the protagonist and then proceeds to show how the Dubrovnik adaptation comically succeeds in making the bores even more boring.